2018
DOI: 10.5194/bg-2017-530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon accumulation in a drained boreal bog was decreased but not stopped by seasonal drought

Abstract: Abstract. Drainage of peatlands is expected to turn these ecosystems to carbon sources to the atmosphere. We measured carbon dynamics of a drained forested peatland in southern Finland over four years, including one with severe drought during 10 growing season. Net ecosystem exchange (NEE) of carbon dioxide (CO2) was measured with eddy covariance method from a mast above the forest. Soil and forest floor CO2 and methane (CH4) fluxes were measured from the strips and from ditches with closed chambers. Biomasses… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Rainfall can be an important climate determinant of peatland CO 2 flux. First, rainfall impact on growing seasons NEE can be reflected in photosynthesis levels (clouds affect sunlight), and GPP variation can affect NEE much more than other climate factors (Hirano et al, ; Minkkinen et al, ; Zhao et al, ). We found that cumulative monthly rainfall correlated significantly with cumulative monthly NEE from 2013 to 2015, but not in 2016 or 2017 (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Rainfall can be an important climate determinant of peatland CO 2 flux. First, rainfall impact on growing seasons NEE can be reflected in photosynthesis levels (clouds affect sunlight), and GPP variation can affect NEE much more than other climate factors (Hirano et al, ; Minkkinen et al, ; Zhao et al, ). We found that cumulative monthly rainfall correlated significantly with cumulative monthly NEE from 2013 to 2015, but not in 2016 or 2017 (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to lower water table, the sites differ from each other in that drained sites have significant amount of tree roots, which are lacking from undrained sites. Based on estimate from a Finnish forestry drained mire, 10 to 20 % of the respiration may be produced by tree roots (Minkkinen et al 2018). In addition to increased respiration rates, drainage decreased the photosynthetic capacity (PMAX) of the field layer vegetation and shifted production to the growing tree stand.…”
Section: Co2 Exchangementioning
confidence: 99%
“…In some forestry drained mires, the growth of the tree stand has exceeded the C release from the decomposing peat, resulting in a large C sink (e.g. Lohila et al 2011;Ojanen et al 2013;Hommeltenberg et al 2014;Minkkinen et al 2018;Ojanen et al unpublished data,). All such sites have been nutrient poor but still able to support intensive tree growth.…”
Section: Co2 Exchangementioning
confidence: 99%